Perancangan Aplikasi Mobile Penjualan Ikan Segar Dengan Pendekatan Design Thinking - Muhammad Yordi Septian; Luthfi Dika Chandra; Muhammad Galuh Gumelar; Irma Rasita Gloria Barus; Amata Fami (SMATIKA JURNAL : STIKI Informatika Jurnal, 2024)
The decline in aquaculture productivity due to the COVID-19 pandemic and increasing global competition, as well as difficulties for fishermen in selling fish due to high distribution costs and low consumer confidence in fish freshness, demand innovative solutions for the fishing industry. This research aims to answer this problem by developing a mobile-based fresh fish marketing application called "FreshCatch." We use Design Thinking methods to improve user experience and interface design. This methodology includes understanding user needs, determining core problems such as the issue of trust in fish freshness, finding solutions, creating low and high-fidelity design prototypes, and usability testing. The research results show a high level of success and user satisfaction with a significant increase in user trust and market accessibility for fishermen. The study concluded that "FreshCatch" effectively enhances the digital transition in fish sales, expands market reach, and increases fish farmers' income while ensuring the availability of fresh fish for consumers. This research contributes to advancing digital solutions in the aquaculture industry, encouraging sustainable and efficient market practices.